APLIKASI ELEKTRONIKA DAYA UNTUK PENGATURAN MOTOR INDUKSI BAGI PARA GURU SMK DI DAERAH ISTIMEWA YOGYAKARTA - Djatmiko, Istanto Wahyu; Ali, Muhammad; Sunomo, Sunomo; Hatmojo, Yuwono Indro (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
Community Service Activity (PPM) on training "Power ElectronicsApplications for Induction Motor Settings for vocational teachers in YogyakartaSpecial Region" conducted at the Laboratory of Power Electronics andElectrical Machine Laboratory in the Department of Electrical EngineeringEducation FT UNY. This activity is conducted by the PPM team consisting oflecturers in the Department of Electrical Engineering Education , FT UNY withthe aim of: (1) provide basic knowledge and skills application of power electronics circuits, namely a series of alternating voltage regulator for inductionmotor control; (2) provide knowledge and skills of the induction motor settingsby utilizing one of the instructional media in the form of a variable speed driveunit; (3) do the programming unit of variable speed drives for induction motorsrotation speed controlling; and (4) do the programming variable speed driveunit for braking the motor induction. PPM activities conducted during the three-day meeting with the allocation for 25 hours. The training material covers the theory and practice include:induction motor theory, the theory of series AC drives, AC drive circuit practice, and practice of induction motor control using Altivar 312. This trainingwas attended by 23 people who had a vocational teacher expertise associatedwith this training. Training method used lectures, discussions, question andanswer, demonstration, and practice directly. The achievement of this result can be expressed PPM activities: (1) theparticipants have increased knowledge and skills in power electronics and itsapplications to induction motor settings are indicated by an increase in the valueof the mean pre-test and post-test participants of 48.9 into 76.5; (2 ) of theparticipants felt the benefits of the PPM activity shown from a mean value of 95 96 3.46 questionnaire scores that can be categorized, this activity is very good; and(3) the participants can develop the training materials as a instructional mediafor the control induction motors